2012
DOI: 10.1007/s10620-012-2330-1
|View full text |Cite
|
Sign up to set email alerts
|

Not All Side Population Cells Contain Cancer Stem-Like Cells in Human Gastric Cancer Cell Lines

Abstract: SP cells from MKN-45 possess cancer stem cell properties and proved that they were gastric cancer stem-like cells. SP cells from BGC-823 didn't possess cancer stem cell properties and proved that not all SP cells contain cancer stem-like cells in gastric cancer cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 26 publications
3
19
0
Order By: Relevance
“…Three human gastric cancer cell lines were used in this study,two CD44-positive cell lines (BGC-823 and SGC-7901) (Xue et al 2012;Zhang et al 2013) and one CD44-negative cell line (MKN-28) (Yokozaki 2000). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Three human gastric cancer cell lines were used in this study,two CD44-positive cell lines (BGC-823 and SGC-7901) (Xue et al 2012;Zhang et al 2013) and one CD44-negative cell line (MKN-28) (Yokozaki 2000). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Zhange et al [47] showed CSC properties in SP cells from the MKN-45 cell line but not the BGC-823 cell line. Although some studies in gastric cancer lines have shown CSC properties in the SP [48,49], others have found no difference compared to a non-SP subset [11,50,51].…”
Section: Side Population Assaymentioning
confidence: 99%
“…In addition, the growth kinetics of SP cells does not differ from those of the non-SP cells [153]. SP cells from the gastric cancer BGC-823 cell line also do not behave as CSCs do [154]. However, some studies have yielded conflicting results.…”
Section: Side Population (Sp) Cellsmentioning
confidence: 99%